2022
DOI: 10.3389/fchem.2022.919552
|View full text |Cite
|
Sign up to set email alerts
|

High Lithium Storage Performance of Co Ion-Doped Li4Ti5O12 Induced by Fast Charge Transport

Abstract: In this study, Co3O4-doped Li4Ti5O12 (LTO) composite was designed and synthesized by the hydrothermal reduction method and metal doping modification method. The microstructure and electrochemical performance of the Co3O4-doped Li4Ti5O12 composite were characterized by XRD, SEM, TEM, electrochemical impedance spectroscopy, and galvanostatic tests. The results showed that Li4Ti5O12 particles attached to lamellar Co3O4 constituted a heterostructure and Co ion doped into Li4Ti5O12 lattice. This Co ion-doped micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…LTO and CTAB were added to 25% alcohol aqueous solution (50 mL of 25% alcohol aqueous solution per 0.1 g LTO) at a mass ratio of 1:1 and ultrasonicated for 2 h. The pH value of GO (prepared by the improved Hummer's method 31 ) solution was adjusted to 8−11 by using 1 mol/L NaOH solution, then slowly added GO into the mixed solution of LTO and CTAB, placed in a 100 mL PTFE lined stainless steel autoclave, and kept at 180 °C for 12 h. After cooling to room temperature, the LTO/rGO composite was obtained by repeated washing with distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LTO and CTAB were added to 25% alcohol aqueous solution (50 mL of 25% alcohol aqueous solution per 0.1 g LTO) at a mass ratio of 1:1 and ultrasonicated for 2 h. The pH value of GO (prepared by the improved Hummer's method 31 ) solution was adjusted to 8−11 by using 1 mol/L NaOH solution, then slowly added GO into the mixed solution of LTO and CTAB, placed in a 100 mL PTFE lined stainless steel autoclave, and kept at 180 °C for 12 h. After cooling to room temperature, the LTO/rGO composite was obtained by repeated washing with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…In order to solve the shortcomings of LTO, some modification methods such as morphology and size improvement, metal ion doping, and surface-coated conductive materials (e.g., carbon nanotubes and biomass carbon) were reported. Zhu et al prepared hollow TiO 2 microspheres by the Ostwald ripening method, and then LTO was synthesized by a simple hydrothermal synthesis method using hollow TiO 2 microspheres as a template. It was found that the hollow LTO microspheres calcined at 700 °C showed good electrochemical performance, including high capacity (174.6 mAh/g at 1C), excellent cycling stability (97.7% capacity retention after 50 cycles at 1C), and remarkable rate capability (140.3 mAh/g at 15C).…”
Section: Introductionmentioning
confidence: 99%